Human Chorionic Gonadotropin: The Pregnancy Hormone and More - Theofanakis, Charalampos (Int J Mol Sci, 2017)
To thoroughly review the uses of human chorionic gonadotropin (hCG) related to the process of reproduction and also assess new, non-traditional theories. Review of the international literature and research studies. hCG and its receptor, LH/CGR, are expressed in numerous sites of the reproductive tract, both in gonadal and extra-goanadal tissues, promoting oocyte maturation, fertilization, implantation and early embryo development. Moreover, hCG seems to have a potential role as an anti-rejection agent in solid organ transplantation. Future research needs to focus extensively on the functions of hCG and its receptor LH/CGR, in an effort to reveal known, as well as unknown clinical potentials.